2019
DOI: 10.1016/j.amsu.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Unique classification of parathyroid dysfunction in patients with transfusion dependent thalassemia major using Nomogram-A cross sectional study

Abstract: Introduction Hypoparathyroidism is a rare complication of iron overload in patients with transfusion dependent β thalassemia major (β-TM). We aim to determine the prevalence of parathyroid dysfunction in patients with β-TM. Methods Diagnosed cases of transfusion dependent β-TM between 5 and 17 years of age were recruited from outpatient clinics of a non-profit organization in Karachi, Pakistan. Blood and urine samples were collected in fasting to determine Ca, P, Alb, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
0
1
1
Order By: Relevance
“…Hypoparathyroidism is reported in 3.6 to 22.5% of patients with BTM (30). If unrecognized or untreated, it may cause decreased bone density, fractures and bone pain, which are often detected in thalassemia, as well as severe hypocalcemia findings (31). In our study, hypoparathyroidism was found 1.6%, lower rate than the literature.…”
Section: Discussioncontrasting
confidence: 52%
“…Hypoparathyroidism is reported in 3.6 to 22.5% of patients with BTM (30). If unrecognized or untreated, it may cause decreased bone density, fractures and bone pain, which are often detected in thalassemia, as well as severe hypocalcemia findings (31). In our study, hypoparathyroidism was found 1.6%, lower rate than the literature.…”
Section: Discussioncontrasting
confidence: 52%
“…В исследовании, прицельно изучавшем нарушения кальций-фосфорного обмена у детей с БТМ, первичный гипопаратиреоз был выявлен у 3,4%, субклинический — у 52,3%, а вторичный — у 34% [ 15 ]. Считается, что причиной гипопаратиреоза может быть как перегрузка паращитовидных желез железом, так и подавление секреции паратгормона вследствие повышенной резорбции костной ткани при активном гемопоэзе на фоне хронической анемии [ 1 ].…”
Section: гипопаратиреозunclassified